(untitled) (Journal of Applied Oral Science, 2021)
SARS-CoV-2 has high human-human transmission rate. The aerosols and saliva droplets are the main contamination source. Thus, it is crucial to point out that dental practitioners become a high-risk group of contagion by SARS-CoV-2. Based on this, protocols have been recommended to avoid cross-contamination during dental care; however, appropriate evidence has not yet been established. Objective: Our study sought to make a screening, by in silico analysis, of the potential of mouth rinses used in dental practices to prevent the dental workers' contamination by SARS-CoV-2. Methodology: Multiple sequence comparisons and construction of the phylogenetic tree were conducted using the FASTA code. Therefore, molecular docking investigation between SARS-CoV-2 proteins (Main Protease, Spike Glycoprotein, Non-structure Protein, and Papain-like Protease) and molecules used in dental practices (chlorhexidine digluconate, hydrogen peroxide, cetylpyridinium chloride, povidone-iodine, gallic acid, β-cyclodextrin, catechin, and quercetin) was performed using AutoDock Vina. Moreover, 2D interactions of the complex protein-ligand structure were analyzed by Ligplot+. Results: The obtained results showed a remarkable affinity between SARS-CoV-2 proteins and all tested compounds. The chlorhexidine digluconate, catechin, and quercetin presented a higher affinity with SARS-CoV-2. Conclusions: The overall results allowed us to suggest that chlorhexidine is the most suitable active compound in reducing the SARS-CoV-2 salivary load due to its better binding energy. However, in vivo studies should be conducted to confirm their clinical use.